An ecological evaluation of the sustainability of bark harvesting of medicinal plant species in the Venda region, Limpopo province, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.